Antigen-specific expansion of cytotoxic T lymphocytes in acute measles virus infection. - Mongkolsapaya, J; Jaye, A; Callan, M; Magnusen, A; McMichael, A; Whittle, H (1999)
Skewing of the T-cell receptor repertoire of CD8(+) T cells has been shown in some persistent infections with viruses, such as human immunodeficiency virus, simian immunodeficiency virus, and Epstein-Barr virus. We have demonstrated that similar distortions also occur in nonpersistent measles virus infection. In addition, two of four children immunized with live, attenuated measles virus showed larger and more persistent CD8(+) T-cell expansions than their naturally infected counterparts. The expanded lymphocyte populations were monoclonal or oligoclonal and lysed target cells infected with recombinant vaccinia virus expressing measles virus protein. These results demonstrate that the expansions of CD8(+) T lymphocytes are antigen driven.